Cell-Cell Connection Enhances Proliferation and Neuronal Differentiation of Rat Embryonic Neural Stem/Progenitor Cells - Qian Jiao; Qian Jiao; Qian Jiao; Xingxing Li; Xingxing Li; Jing An; Jing An; Zhichao Zhang; Zhichao Zhang; Xinlin Chen; Xinlin Chen; Jing Tan; et al. (Frontiers in Cellular Neuroscience, 2017)
Cell-cell interaction as one of the niche signals plays an important role in the balance of stem cell quiescence and proliferation or differentiation. In order to address the effect and the possible mechanisms of cell-cell connection on neural stem/progenitor cells (NSCs/NPCs) proliferation and differentiation, upon passaging, NSCs/NPCs were either dissociated into single cell as usual (named Group I) or mechanically triturated into a mixture of single cell and small cell clusters containing direct cell-cell connections (named Group II). Then the biological behaviors including proliferation and differentiation of NSCs/NPCs were observed. Moreover, the expression of gap junction channel, neurotrophic factors and the phosphorylation status of MAPK signals were compared to investigate the possible mechanisms. Our results showed that, in comparison to the counterparts in Group I, NSCs/NPCs in Group II survived well with preferable neuronal differentiation. In coincidence with this, the expression of connexin 45 (Cx45), as well as brain derived neurotrophic factor (BDNF) and neurotrophin 3 (NT-3) in Group II were significantly higher than those in Group I. Phosphorylation of ERK1/2 and JNK2 were significantly upregulated in Group II too, while no change was found about p38. Furthermore, the differences of NSCs/NPCs biological behaviors between Group I and II completely disappeared when ERK and JNK phosphorylation were inhibited. These results indicated that cell-cell connection in Group II enhanced NSCs/NPCs survival, proliferation and neuronal differentiation through upregulating the expression of gap junction and neurotrophic factors. MAPK signals- ERK and JNK might contribute to the enhancement. Efforts for maintaining the direct cell-cell connection are worth making to provide more favorable niches for NSCs/NPCs survival, proliferation and neuronal differentiation.